A Framework for Assessing Food System Governance in Six Urban and Peri-Urban Regions in Sub-saharan Africa - Chen, Qiuzhen; Knickel, Karlheinz; Tesfai, Mehreteab; Sumelius, John; Turinawe, Alice; Isoto, Rosemary Emegu; Medyna, Galyna (Frontiers in Sustainable Food Systems, 2021)
An important goal across Sub-Saharan Africa (SSA), and globally, is to foster a healthy nutrition. A strengthening of the diversity, sustainability, resilience and connectivity of food systems is increasingly seen as a key leverage point. Governance arrangements play a central role in connecting sustainable, resilient farming with healthy nutrition. In this article, we elaborate a framework for assessing, monitoring and improving the governance of food systems. Our focus is on food chains in six peri-urban and urban regions in SSA. A literature review on food chain governance and a mapping of current agri-food chains in the six regions provide the basis for the elaboration of an indicator-based assessment framework. The framework is adapted to the specific conditions of SSA and related goals. The assessment framework is then used to identify the challenges and opportunities in food chain governance in the six regions. The first testing of the framework indicates that the approach can help to identify disconnects, conflicting goals and tensions in food systems, and to formulate strategies for empowering agri-food chain actors in transitioning towards more efficient, equitable and sustainable agri-food systems. The article is concluded with a brief reflection on the strengths and weaknesses of the framework and suggests further testing and refinement.